LAPORAN CSR: VOLUNTARY atau MANDATORY? Studi Kasus: Perbandingan Laporan CSR On-line antara Indonesia dan Swedia - Caroline Nathania Kwenusland; Dianne Frisko (Jurnal Akuntansi Bisnis, 2017)
Corporate Social Responsibility (CSR) has become one consideration to determine performance of companies. As social responsibility, some companies assume that it become mandatory to conduct, while others believe it suppose to be an ethics that embedded with company’s existence in business activities. This study aims to analyze through comparison study on CSR practice as voluntary in most developed countries, with it mandatory practice in developing countries. This study used a qualitative approach and content analysis method by analyzing of websites, documents, journals, and information published in public domain,refer to Sweden and Indonesia as comparison object. The results asserted there are significant differences pertaining with CSR regulatory between developed and developing country, which affect the reporting of CSR in both countries.Key words : CSR, Regulation, Sustainability Report